Modulatory Effects of Eschscholzia californica Alkaloids on Recombinant GABAA Receptors - Milan Fedurco; Jana Gregorová; Kristýna Šebrlová; Jana Kantorová; Ondřej Peš; Roland Baur; Erwin Sigel; Eva Táborská (Biochemistry Research International)
The California poppy (Eschscholzia californica Cham.) contains a variety of natural compounds including several alkaloids found exclusively in this plant. Because of the sedative, anxiolytic, and analgesic effects, this herb is currently sold in pharmacies in many countries. However, our understanding of these biological effects at the molecular level is still lacking. Alkaloids detected in E. californica could be hypothesized to act at GABAA receptors, which are widely expressed in the brain mainly at the inhibitory interneurons. Electrophysiological studies on a recombinant α1β2γ2 GABAA receptor showed no effect of N-methyllaurotetanine at concentrations lower than 30 μM. However, (S)-reticuline behaved as positive allosteric modulator at the α3, α5, and α6 isoforms of GABAA receptors. The depressant properties of aerial parts of E. californica are assigned to chloride-current modulation by (S)-reticuline at the α3β2γ2 and α5β2γ2 GABAA receptors. Interestingly, α1, α3, and α5 were not significantly affected by (R)-reticuline, 1,2-tetrahydroreticuline, codeine, and morphine—suspected (S)-reticuline metabolites in the rodent brain.